Performance Measurement of Public Art Museums - Prokůpek, Marek, 1987- (2017)
The issue of the economics of cultural institutions, their economic impact, and measurement of their performance has been paid systematic attention basically only in the past few years. PhD thesis analyses the methods of performance measurement in public art museums and creates economic models. Aim of my thesis is also to create a model for museum managers to measure the performance. Nowadays it is almost necessary to integrate performance measurement system in organization´s strategy decision making. The museum managers feel the pressure to prove that their organization is performing well by various stakeholders and we perceive the idea that multidimensional performance measures could fill the informational gap concerning performance, quality, and the artistic value of cultural programs. The mixed research method was employed in this research. Qualitative data was obtained from the questionnaire and interviews. Quantitative data was obtained from the questionnaire, annual reports and reports of The National Information and Consulting Centre for Culture (NIPOS). The aim of this study is to propose a comprehensive multidimensional model to assess art museum activities. This model takes into account the scope and character of museum´s mission. This model consists of implementation of Data Envelopment Analysis into Balanced Scorecard.